2015
DOI: 10.1002/for.2350
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Model Averaging and CPI Inflation Forecasts: A Comparison between the Euro Area and the United States

Abstract: The paper forecasts consumer price inflation in the euro area (EA) and in the USA between 1980:Q1 and 2012:Q4 based on a large set of predictors, with dynamic model averaging (DMA) and dynamic model selection (DMS). DMA/DMS allows not solely for coefficients to change over time, but also for changes in the entire forecasting model over time. DMA/DMS provides on average the best inflation forecasts with regard to alternative approaches (such as the random walk). DMS outperforms DMA. These results are robust for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 60 publications
1
16
0
Order By: Relevance
“…Here, the authors found the DMA technique to be significantly better than benchmark regression models and selected time varying coefficient models. In [2], both the DMA technique and Dynamic Model Selection (DMS) were used to improve inflation forecasts for USA and the Euro area. In contrast, the Bayesian Model Averaging (BMA) technique is yet another popular form of forecast combination and was utilized in [5] for forecasting US inflation forecasting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 3 more Smart Citations
“…Here, the authors found the DMA technique to be significantly better than benchmark regression models and selected time varying coefficient models. In [2], both the DMA technique and Dynamic Model Selection (DMS) were used to improve inflation forecasts for USA and the Euro area. In contrast, the Bayesian Model Averaging (BMA) technique is yet another popular form of forecast combination and was utilized in [5] for forecasting US inflation forecasting.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Nevertheless, a review of the relevant literature points out towards the existence of a strong heterogeneity in the predictive performances of the models used for inflation forecasting [2]. Thus, our interest delves into the search for a new and improved approach for improving the accuracy of inflation forecasts.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations
“…First, the existence of many potential predictors can result in a huge number of potential models. Studies that use DMA to forecast a variety of different economic time series include: Buncic and Moretto (2015), Drachal (2016), and Naser (2016), forecasting commodities; Bruyn, Gupta, and Eyden (2015), Beckmann and Schüssler (2016), and Byrne, Korobilis, and Ribeiro (2018), forecasting exchange rates; Liu, Ma, and Wang (2015), forecasting stock returns; Gupta, Hammoudeh, Kim, and Simo-Kengne (2014), forecasting foreign exchange reserves; Bork and Moller (2015), Risse and Kern (2016), and Wei and Cao (2017), forecasting house price growth; Aye, Gupta, Hammoudeh, and Joong (2015) and Baur, Beckmann, and Czudaj (2016) forecasting gold prices; Koop and Korobilis (2011) and Filippo (2015), forecasting inflation; and Wang, Ma, Wei, and Wu (2016) and Liu, Wei, Y., Ma, F., and Wahab (2017), forecasting realized volatility. This leads to the need for model selection strategies.…”
Section: Introductionmentioning
confidence: 99%